Community Service in Kiria B Farmers' Group, Bhera Village, Mego District, Sikka District Concerning the Integration of Gender Perspectives in Agriculture Policies and Practices in Farmers' Groups (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Gender equality is a movement that is voiced to fight for the fate of women, initially this concept emerged because of injustice and discrimination that sees gender as a measure of roles in society, the placement of women in the social system does not immediately eliminate the role of women in the social order. Such conditions are an opportunity for women to emancipate and stop perpetuating the patriarchal system that has been carried out by society, with the existence of the emancipation movement, women progressively change the social and cultural system without eliminating the dignity of a man. Integration of gender perspectives in agricultural policies and practices is very important to ensure that everyone, both men and women, can feel the same benefits from the agricultural sector. This includes recognizing the diverse roles and contributions of gender in agriculture, as well as ensuring equal access to resources, information, and opportunities. The topic raised in the socialization activity in Bhera Village, Mego District, Sikka Regency was the Integration of Gender Perspectives in Agricultural Policies and Practices in Farmer Groups.The purpose of this socialization is to ensure that all members of the farmer group, both men and women, have equal and fair opportunities in accessing resources, information, services, and benefits from the agricultural sector. In addition, gender integration aims to increase the effectiveness and sustainability of agricultural development by considering differences in needs and gender roles in the production process, marketing, and management of natural resources. The methods used in this Socialization activity are: Integration of Gender Perspectives in Agricultural Policies and Practices in Farmer Groups. And secondly, conducting discussions with the target audience (Women and men in the Kiria B Farmer Group, Bhera Village).